A Unique Frustrated Lewis Pair Pathway to Remarkably Stable Borata–Alkene Systems. Issue 19 (5th June 2013) - Yu, Jiangang; Kehr, Gerald; Daniliuc, Constantin G.; Erker, Gerhard
Abstract: The hydroboration of a conjugated diphenylphosphanylenyne with Piers' borane [HB(C6 F5 )2 ] gives three products. The major product is probably formed by generation of a geminal P/B frustrated Lewis pair that undergoes rapid and subsequent intramolecular conjugate addition of the phosphane to the dienyl borane unit to yield a unique phosphonium borata–diene. The minor products originate from alternative regioisomeric hydroboration reactions. Two examples of the new phosphonium borata–olefin products were characterized by X‐ray diffraction. Abstract : The hydroboration of a diphenylphosphanylenyne with Piers' borane at elevated temperature gives a zwitterionic borata–alkene. This unique reaction yields borata–alkenes without the need of α‐boryl deprotonation.